Accessing occupational health services in the Southern African development community region - Masekameni, Masilu Daniel; Moyo, Dingani; Khoza, Norman; Chamdimba, Chimwemwe (MDPI AG, 2021)
Only 15% of the global population has access to occupational safety and health services. In Africa, only 5% of employees working from major establishments have access to occupational health services (OHS). Access to primary health care (PHC) services is addressed in many settings and inclusion of OHS in these facilities might increase efficiency in preventing occupational diseases. A cross-sectional study was conducted in four Southern African Development Community (SADC) countries aiming at assessing the availability of OHS at PHC facilities and the organization of OHS. We conducted a literature review to assess the provision and organization of OHS services. In addition to the review, a total of 23 doctors from Zambia were interviewed using questionnaires in order to determine the availability of OHS and training. Consultations with heads of ministries were done in four SADC countries. Results showed that in the SADC region, OHS are fragmented and lack a comprehensive approach. In addition, out of 23 PHC facilities, only two (13%) provided occupational health and PHC. However, OHS provided at PHC facilities were limited to TB screening and audiometric testing. Our study showed a huge inadequacy of trained occupational health practitioners. This study supports the World Health Organization’s advocacy to integrate OHS at the PHC level.